TOXICITY PROFILE AND CHEMICAL CONSTITUENTS OF THE INGREDIENTS OF A SIDDHA DRUG - KANDHAGA RASAYANAM - MEENA R; RAMASWAMY RS (International Journal of Pharma and Bio Sciences, 2015)
Siddha system of medicine is a traditional system practised among Tamil speaking people of India. Siddhars, the ancient scientists are the founders of this system. Herbs, minerals/metals and animal products are used in medicine preparation. Kandhga Rasayanam is a herbo mineral drug mentioned in classic Siddha text. It is used in treating skin diseases, urinary infections, venereal diseases, arthritis etc. The present review is aimed to collect information about toxicity studies and phytoconstituents substantiating the traditional claim of safety and efficacy. Most of the herbal drugs were found to be nontoxic and rich in secondary metabolites responsible for antimicrobial, antifungal and antioxidant properties. This compound drug mentioned in Siddha literature is thus validated.